Electron transport layer and preparation method thereof, perovskite cell and preparation method thereof

By controlling the concentration of hydrohalogenic acid and chelating agent in the mother liquor of stannous halogenated salt and urea, a high-purity SnO2 electron transport layer was prepared, which solved the problem of insufficient purity and crystallinity of the electron transport layer in perovskite solar cells and improved the battery stability and photoelectric conversion efficiency.

CN119255626APending Publication Date: 2025-01-03TRINA SOLAR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411358096.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The electron transport layer of existing perovskite solar cells has shortcomings in terms of purity, crystallinity and stability, which affects its photoelectric conversion efficiency and service life.

Method used

Using a preparation method, by configuring the mother liquor of stannous halide salt and urea, and adding hydrohalogenic acid and chelating agent, the deposition process is controlled to prepare a high-purity and crystalline SnO2 electron transport layer, combined with ultrasonic treatment and annealing treatment, Enhance the bonding ability to the substrate.

Benefits of technology

A high-purity, density, uniform and continuous electron transport layer is achieved, which improves the electrical and optical properties of perovskite batteries and extends the service life and stability of the batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119255626A_ABST
    Figure CN119255626A_ABST
Patent Text Reader

Abstract

The invention provides an electron transport layer and a preparation method thereof, and a perovskite cell and a preparation method thereof, and the preparation method of the electron transport layer comprises the steps: preparing a first mother solution, the solute of the first mother solution being one or more stannous halide salts, and the solvent of the first mother solution being an acid containing sulfydryl; a solute of the second mother liquor is urea, and a solvent of the second mother liquor is purified water; the first mother liquor and the second mother liquor are mixed, halogen acid is added and stirred to be dissolved, third mother liquor is formed, and halogen elements in the halogen acid are the same as those in the stannous halide salt; and adding a chelating agent into the third mother solution, dissolving and diluting, and putting a substrate of a to-be-prepared electron transport layer into the third mother solution with the chelating agent to prepare the electron transport layer. The electron transport layer which is high in purity, good in crystallinity, high in density, uniform and continuous can be prepared, the electron transport layer has good conductivity and transparency, the bonding capacity between the electron transport layer and the substrate is enhanced, the stability of the perovskite cell is improved, and the service life of the perovskite cell is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention mainly relates to the technical field of solar cells, and in particular to an electron transport layer and a preparation method thereof, a perovskite cell and a preparation method thereof. Background Art

[0002] The electron transport layer of perovskite solar cells (PSCs) plays a vital role in determining its photoelectric conversion efficiency and stability. This layer is mainly responsible for quickly extracting and transporting electrons from the photoactive perovskite layer while preventing electron-hole recombination. Currently commonly used electron transport materials mainly include wide bandgap semiconductor materials such as titanium dioxide (TiO2) and nickel oxide (NiO). Among them, TiO2 has become the most widely used electron transport layer material due to its good chemical stability and suitable energy level position. However, the preparation process of TiO2 is complicated and has certain requirements on the crystallinity of the perovskite layer, which has prompted researchers to seek better alternatives.

[0003] Tin dioxide (SnO2) has excellent properties such as higher electron mobility, wider band gap and more stable optical properties. Currently, SnO2 is used to replace TiO2 as ETL (Electron Transport Layer), and the chemical bath deposition (CBD) method has been widely used to prepare high-quality SnO2 films, which provides support for achieving breakthroughs in the PCE (power conversion efficiency) of planar PSCs. However, the traditional CBD method is difficult to control the reaction rate and cannot ensure high-quality SnO2 films with high repeatability. In addition, the presence of Sn interstitial atoms, oxygen atom vacancies and hydroxyl groups in the electron transport layer will cause serious carrier recombination, limiting the performance of PSCs.

[0004] In 2023, Moungi.G.Bawendi et al. from the Massachusetts Institute of Technology used volatile dicarboxylic acid ligand oxalic acid to introduce a chemical bath method to prepare thin film tin oxide to replace traditional thioglycolic acid, and applied H2O2 post-treatment to synergistically remove chemical residues and passivate surface oxygen vacancies, and finally prepared a champion device with a power conversion efficiency of 24.6%. Life tests show that the device based on the oxalic acid CBD method for preparing tin oxide maintained an efficiency of 85% without cooling after 1500 hours of MPP (maximum power point) tracking under continuous sunlight, which is significantly improved compared to the traditional thioglycolic acid-based CBD method for preparing tin oxide control devices. However, impurity ions may be introduced during the chemical bath deposition process, resulting in limited purity of the prepared tin oxide film, and the crystal structure and crystallinity may not be ideal, affecting its electrical and optical properties. During the crystal growth process, due to factors such as thermal motion, Sn atoms may occupy interstitial positions in the lattice to form interstitial atoms. These interstitial atoms will destroy the integrity of the SnO2 lattice and produce deep energy level impurity states, thus becoming non-radiative recombination centers, increasing the probability of carrier recombination, and reducing the photoelectric properties of the film. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide an electron transport layer and a preparation method, a perovskite battery and a preparation method, which can prepare an electron transport layer with high purity, good crystallinity, high density, uniformity and continuity. The electron transport layer has good conductivity and transparency, and enhances the bonding ability with the substrate.

[0006] To solve the above technical problems, in a first aspect, the present invention provides a method for preparing an electron transport layer, comprising: preparing a first mother liquor, wherein the solute of the first mother liquor is one or more stannous halide salts, and the solvent of the first mother liquor is an acid containing a thiol group; preparing a second mother liquor, wherein the solute of the second mother liquor is urea, and the solvent of the second mother liquor is pure water; mixing the first mother liquor and the second mother liquor, and then adding hydrohalic acid to stir and dissolve to form a third mother liquor, wherein the halogen element in the hydrohalic acid is the same as the halogen element in the stannous halide salt; adding a chelating agent to the third mother liquor to dissolve and dilute, placing the substrate on which the electron transport layer is to be prepared into the third mother liquor having the chelating agent, and preparing the electron transport layer.

[0007] Optionally, when preparing the first mother solution, the concentration of the first mother solution is between 3 mmol / L and 5 mmol / L.

[0008] Optionally, when preparing the second mother liquor, the concentration of the second mother liquor is between 0.2 mmol / L and 0.3 mmol / L.

[0009] Optionally, when preparing the third mother liquor, the concentration of the hydrohalic acid is between 0.01 mmol / L and 1 mmol / L.

[0010] Optionally, the substrate on which the electron transport layer is to be prepared is placed in a third mother liquor having the chelating agent, and the preparation of the electron transport layer includes: placing the substrate on which the electron transport layer is to be prepared in the third mother liquor having the chelating agent, and after the hydrolysis is completed, rinsing the substrate with pure water, then performing ultrasonic treatment, and performing annealing after drying to obtain the SnO2 electron transport layer.

[0011] Optionally, the hydrolysis time of the substrate after being placed in the third mother solution containing the chelating agent is between 1.5 h and 2 h, and / or the annealing temperature of the annealing treatment after drying is between 150° C. and 170° C.

[0012] Optionally, in the step of adding a chelating agent to the third mother liquor to dissolve and dilute, the concentration of the chelating agent is between 0.3 mg / ml and 2 mg / ml.

[0013] Optionally, the chelating agent is one or both of tetrasodium ethylenediaminetetraacetate and trisodium hydroxyethylethylenediaminetriacetate.

[0014] In a second aspect, the present invention provides an electron transport layer prepared by the method for preparing an electron transport layer described in the first aspect.

[0015] In a third aspect, the present invention provides a method for preparing a perovskite battery, comprising: preparing ITO conductive glass; preparing an electron transport layer SnO2 by a chemical bath deposition method, wherein the electron transport layer SnO2 is prepared by the preparation method of the first aspect; preparing a FAPbI3 perovskite light absorbing layer by a spin coating method; preparing a hole transport layer Sprio-OMeTAD by a spin coating method; preparing MoO3 by a thermal evaporation method; and preparing an Ag electrode by a thermal evaporation method.

[0016] In a fourth aspect, the present invention provides a perovskite cell prepared by the preparation method described in the third aspect, wherein the perovskite cell structure sequentially comprises glass, a transparent conductive oxide layer, a SnO2 electron transport layer, a perovskite light absorption layer, a hole transport layer and an electrode.

[0017] Optionally, the transparent conductive oxide layer includes one of the following materials: ITO, IZO, IWO, FTO, ICO, AZO and BZO.

[0018] Optionally, the perovskite light absorbing layer has a thickness of 10 nm to 100 μm and a band gap of 0.9 eV to 3.0 eV.

[0019] Compared with the prior art, the present invention has the following advantages: by controlling the concentration of the chelating agent to adjust the SnO2 deposition process, the grain size, morphology and crystal orientation of the film are affected, thereby optimizing the electrical and optical properties of the SnO2 film, and being able to prepare a high-purity, good-crystallinity, high-density, uniform and continuous electron transport layer, the electron transport layer has good conductivity and transparency, and enhances the bonding ability with the substrate (or baseboard), which helps to improve the stability and service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The accompanying drawings are included to provide a further understanding of the present application. They are included and constitute a part of the present application. The accompanying drawings illustrate embodiments of the present application and together with the present specification serve to explain the principles of the present application. In the accompanying drawings:

[0021] Figure 1 is a schematic flow chart of a method for preparing an electron transport layer according to an embodiment of the present invention;

[0022] Figure 2 is a schematic flow chart of a method for preparing an electron transport layer according to another embodiment of the present invention;

[0023] Figure 3 It is a schematic diagram of the structure of a perovskite battery prepared according to an embodiment of the present invention. DETAILED DESCRIPTION

[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following is a brief introduction to the drawings required for the description of the embodiments. Obviously, the drawings described below are only some examples or embodiments of the present application. For ordinary technicians in this field, the present application can also be applied to other similar scenarios based on these drawings without creative work. Unless it is obvious from the language environment or otherwise explained, the same reference numerals in the figures represent the same structure or operation.

[0025] As shown in this application and claims, unless the context clearly indicates an exception, the words "a", "an", "an" and / or "the" do not refer to the singular and may also include the plural. Generally speaking, the terms "include" and "comprise" only indicate the inclusion of the steps and elements that have been clearly identified, and these steps and elements do not constitute an exclusive list. The method or device may also include other steps or elements.

[0026] In addition, it should be noted that the use of words such as "first" and "second" to define components is only for the convenience of distinguishing the corresponding components. If not otherwise stated, the above words have no special meaning and cannot be understood as limiting the scope of protection of this application. In addition, although the terms used in this application are selected from well-known and commonly used terms, some terms mentioned in the specification of this application may be selected by the applicant at his or her discretion, and their detailed meanings are explained in the relevant parts of the description of this article. In addition, it is required to understand this application not only by the actual terms used, but also by the meaning implied by each term.

[0027] Flowcharts are used in the present application to illustrate the operations performed by the system according to the embodiments of the present application. It should be understood that the preceding or following operations are not necessarily performed accurately in order. On the contrary, various steps may be processed in reverse order or simultaneously. At the same time, other operations may be added to these processes, or one or more operations may be removed from these processes.

[0028] Figure 1 is a schematic diagram of a method for preparing an electron transport layer according to an embodiment of the present invention, with reference to Figure 1 As shown, method 100 includes: S110, preparing a first mother liquor, wherein the solute of the first mother liquor is one or more stannous halide salts, such as SnCl2 or a combination of SnCl2 and other stannous halide salts, and the solvent of the first mother liquor is an acid containing a thiol group, such as thioacetic acid, thiopropionic acid, thiobutyric acid, thioethanesulfonic acid, thioisobutyric acid, etc.; S120, preparing a second mother liquor, wherein the solute of the second mother liquor is urea, and the solvent of the second mother liquor is pure water; S130, mixing the first mother liquor and the second mother liquor, and then adding a hydrohalic acid to stir and dissolve to form a third mother liquor, wherein the halogen element in the hydrohalic acid is the same as the halogen element in the stannous halide salt, and the hydrohalic acid can be hydrochloric acid, hydrobromic acid, hydroiodic acid, etc.; S140, adding a chelating agent to the third mother liquor to dissolve and dilute, placing the substrate to be prepared with the electron transport layer into the third mother liquor with the chelating agent, and preparing the electron transport layer.

[0029] In this embodiment, the chelating agent can inhibit the excessive growth of SnO2 grains and promote the formation of a fine and uniform grain structure. This nanoscale grain structure helps to improve electron mobility because the smaller grain size can shorten the distance that electrons travel across grain boundaries and reduce electron scattering, thereby improving electron transmission efficiency.

[0030] In one example, when preparing the first mother solution, the concentration of the first mother solution is between 3 mmol / L and 5 mmol / L. For example, one portion of the first mother solution is prepared from 550 mg SnCl2 and 800 μl thioglycolic acid.

[0031] In one example, when preparing the second mother solution, the concentration of the second mother solution is between 0.2 mmol / L and 0.3 mmol / L. For example, one portion of the second mother solution is prepared from 2.5 g of urea and 200 ml of pure ice.

[0032] In one example, when preparing the third mother solution, the concentration of the hydrohalic acid is between 0.01 mmol / L and 1 mmol / L. For example, one portion of the third mother solution is prepared from one portion of the first mother solution, one portion of the second mother solution and 2.5 ml of hydrochloric acid.

[0033] In one example, in the step of adding a chelating agent to the third mother liquor to dissolve and dilute, one part of the third mother liquor is diluted by adding 5 parts of ice water.

[0034] The concentration of the solution directly affects the supply of the reactant, thereby affecting the nucleation rate and the growth rate of the crystal. A higher concentration can increase the number of reactants arriving at the substrate surface per unit time, promote rapid nucleation and growth, and may lead to a higher nucleation density and a faster growth rate. However, too high a concentration may also cause nucleation to be too fast, forming a large number of small, uneven particles, rather than the desired large grain structure. The morphology of the final deposited layer (such as flatness, roughness, porosity, etc.) has a significant impact. During the chemical bath deposition process, the concentration of the solute also affects the dissolution and doping efficiency of impurities. High concentrations may cause uneven distribution of impurities, affecting the purity and electrical and optical properties of the material. The method of this embodiment preferably configures the above-mentioned concentrations. Of course, other concentrations may also be configured in consideration of actual environmental factors, cost control, and performance requirements, and this embodiment does not specifically limit this.

[0035] In one example, a substrate on which an electron transport layer is to be prepared is placed in a third mother liquor having a chelating agent, and preparing the electron transport layer includes: placing the substrate on which an electron transport layer is to be prepared in a third mother liquor having a chelating agent, and after hydrolysis is completed, rinsing the substrate with pure water, and then performing ultrasonic treatment, and then performing annealing treatment after drying to obtain a SnO2 electron transport layer.

[0036] In one example, the hydrolysis time after the substrate is placed in the third mother solution containing the chelating agent is between 1.5 hours and 2 hours, and / or the annealing temperature after drying is between 150° C. and 170° C.

[0037] The length of the hydrolysis time is affected by many factors, including the type of raw materials, hydrolysis conditions, type and concentration of the hydrolyzing agent, etc. In practical applications, it is necessary to determine the appropriate hydrolysis time based on the specific raw materials, hydrolysis conditions and goals.

[0038] In one example, in the step of adding a chelating agent to the third mother solution to dissolve and dilute the solution, the concentration of the chelating agent is between 0.3 mg / ml and 2 mg / ml.

[0039] In one example, the chelating agent is one or both of tetrasodium ethylenediaminetetraacetate and trisodium hydroxyethylethylenediaminetriacetate.

[0040] In this embodiment, ethylenediaminetetraacetic acid tetrasodium (EDTA-4Na) or hydroxyethylethylenediaminetriacetic acid trisodium (HEDTA-3Na) chelating agent is used for preparing tin dioxide electron transport layer by chemical bath deposition method. Its advantage is that EDTA-4Na and HEDTA-3Na can form stable water-soluble complexes with anions and cations in the SnO2 preparation mother solution, thereby effectively removing impurities, and can significantly improve the crystallinity and purity of the obtained SnO2 film, which is beneficial to improving the electrical properties and stability of the electron transport layer.

[0041] In addition, the presence of chelating agents can improve the dispersibility of SnO2 in the precursor solution, making it easier to coat evenly during the film formation process, thereby improving the thickness uniformity and surface flatness of the SnO2 film, which is beneficial to reducing the interface resistance and enhancing the uniformity of electron transfer, which is crucial to the overall performance of the device.

[0042] Exemplarily, the SnO2 electron transport layer is prepared by chemical bath deposition, as follows: 1) the glass and transparent conductive substrate are cleaned and blown dry by air blowing; 2) the first mother liquor is prepared: 550 mg of SnCl2 is weighed and placed in a sample bottle, 800 ul of thioglycolic acid is placed in a bottle and stirred to dissolve; 3) the second mother liquor is prepared: 2.5 g of urea is weighed, 200 ml of pure ice water is poured into a Shu Niu bottle to dissolve the urea; 4) the first mother liquor and the second mother liquor are evenly mixed, and then 2.5 ml of hydrochloric acid is added and stirred to dissolve, and after dissolution, it is placed in a refrigerator for refrigeration; 5) 30 ml of the mixed mother liquor is placed in a container, an appropriate amount of chelating agent is added to dissolve, and diluted with 150 ml of ice water; 6) the treated substrate is placed in a container, the container is sealed and then ultrasonically treated to remove bubbles; 7) it is placed in a 90°C oven for hydrolysis treatment; 8) after the hydrolysis is completed, the substrate is repeatedly rinsed with pure water, and then ultrasonically treated.

[0043] As shown in Table 1 and Table 2, this example compares the roughness of SnO2 films and the photoelectric performance parameters of the prepared devices under different preparation methods, among which V OC represents the open circuit voltage, J SC represents short-circuit current density, FF represents fill factor, and PCE represents photoelectric conversion efficiency.

[0044] Table 1 Comparison of surface roughness of SnO2 prepared under different conditions

[0045]

[0046] Table 2 Preparation of SnO2 electron transport layer under different conditions and its related battery performance

[0047] Voc(V) <![CDATA[Jsc(mA / cm 2 )]]> FF(%) PCE(%) Crl (process without relevant chelating agent addition) 1.151 25.48 81.14 23.80 Add 0.5mg / ml EDTA-4Na chelating agent 1.194 25.51 81.63 24.86 Add 2mg / ml EDTA-4Na chelating agent 1.202 25.52 81.74 25.07 Add 0.5mg / ml HEDTA-3Na chelating agent 1.196 25.48 81.51 24.84 Add 2mg / ml HEDTA-3Na chelating agent 1.194 25.52 81.65 24.88

[0048] An embodiment of the present invention further provides an electron transport layer, which is prepared by the above-mentioned method for preparing the electron transport layer. The relevant details of the electron transport layer are not repeated here.

[0049] The preparation method of the electron transport layer in this embodiment adjusts the SnO2 deposition process by controlling the concentration of the chelating agent, thereby affecting the grain size, morphology and crystal orientation of the film, and further optimizing the electrical and optical properties of the SnO2 film. A high-purity, good-crystallinity, high-density, uniform and continuous electron transport layer can be prepared. The electron transport layer has good conductivity and transparency, and enhances the bonding ability with the substrate, which helps to improve the stability and service life of the battery.

[0050] Another embodiment of the present invention provides a method for preparing a perovskite battery, referring to Figure 2 As shown, method 200 includes: S210, preparing ITO conductive glass; S220, preparing an electron transport layer SnO2 by chemical bath deposition, wherein the electron transport layer SnO2 is prepared by the electron transport layer preparation method of the aforementioned embodiment; S230, preparing a FAPbI3 perovskite light absorbing layer by spin coating; S240, preparing a hole transport layer Sprio-OMeTAD by spin coating; S250, preparing MoO3 by thermal evaporation; S260, preparing an Ag electrode by thermal evaporation.

[0051] Exemplarily, a method for preparing a perovskite battery using a chelating agent to modify an electron transport layer includes: 1) preparing ITO conductive glass with a thickness of 0.7 mm; 2) preparing an electron transport layer SnO2 with a thickness of 15 nm by chemical bath deposition, and the electron transport layer is prepared by the preparation method of the electron transport layer in the previous embodiment, which is not repeated here; 3) preparing a FAPbI3 perovskite light absorption layer by spin coating with a thickness of 600 nm; 4) preparing a hole transport layer Sprio-OMeTAD by spin coating with a thickness of 200 nm; 5) preparing MoO3 by thermal evaporation with a thickness of 10 nm; 6) preparing an Ag electrode by thermal evaporation with a thickness of 150 nm.

[0052] An embodiment of the present invention provides a perovskite battery, which is prepared by the above-mentioned perovskite battery preparation method, referring to Figure 3 As shown, the perovskite cell structure includes glass, a transparent conductive oxide layer, a SnO2 electron transport layer, a perovskite light absorption layer, a hole transport layer and an electrode in sequence.

[0053] In one example, the transparent conductive oxide layer includes one of the following materials: ITO, IZO, IWO, FTO, ICO, AZO, and BZO.

[0054] In one example, the thickness of the perovskite light absorbing layer is 10 nm to 100 μm, and the band gap is 0.9 eV to 3.0 eV.

[0055] In this embodiment, the perovskite is a three-dimensional structure ABX3, A is a monovalent cation, including one or more monovalent cation mixtures of cesium (Cs), rubidium (Rb), methylamine (CH3NH3), and methylamidine (CH2(NH2)2); B is a divalent cation, including one or more divalent cation mixtures of lead (Pb), copper (Cu), zinc (Zn), gallium (Ga), tin (Sn), and calcium (Ca); X is a monovalent anion, including one or more monovalent anion mixtures of iodine (I), bromine (Br), chlorine (Cl), fluorine (F), and thiocyanate ion (SCN). It should be understood that those skilled in the art can make corresponding adjustments to the content of each part in the above-mentioned compound according to actual needs, and this embodiment does not specifically limit this.

[0056] In this embodiment, the hole transport layer includes one or more of the following materials: [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACz), [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz), [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz), benzoic acid, 4-[bis(2,4-dimethoxybiphenyl-4-yl)]phosphonic acid (Me-4PACz), )amino]-biphenyl-4-carboxylic acid [MC-43], etc., Spiro-OMeTAD (2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene), PTAA (polyethylene terephthalate), P3HT (polymer of 3-hexylthiophene), PEDOT:PSS, Spiro-TTB, F4-TCNQ, F6TCNNQ, TAPC, ATO, NiO x , CuSCN, CuAlO2, V2O5, CdS, CdSe.

[0057] In this embodiment, the electrode material includes one or more of the following materials: Au, Ag, Al, Cu, graphene, TCO material, nanocrystalline silicon, and the electrode preparation method includes: one or more of spin coating, scraping, evaporation, printing, spraying, spray pyrolysis, and slit coating.

[0058] The perovskite battery preparation method of this embodiment, wherein when preparing the electron transport layer, the SnO2 deposition process is adjusted by controlling the concentration of the chelating agent, thereby affecting the grain size, morphology and crystal orientation of the film, and further optimizing the electrical and optical properties of the SnO2 film, and can prepare a high-purity, good crystallinity, high-density, uniform and continuous electron transport layer. The electron transport layer has good conductivity and transparency, enhances the bonding ability with the substrate, and helps to improve the stability and service life of the battery.

[0059] The basic concepts have been described above. Obviously, for those skilled in the art, the above invention disclosure is only used as an example and does not constitute a limitation of the present application. Although not explicitly stated herein, those skilled in the art may make various modifications, improvements and amendments to the present application. Such modifications, improvements and amendments are suggested in the present application, so such modifications, improvements and amendments still belong to the spirit and scope of the exemplary embodiments of the present application.

[0060] At the same time, the present application uses specific words to describe the embodiments of the present application. For example, "one embodiment", "an embodiment", and / or "some embodiments" refer to a certain feature, structure or characteristic related to at least one embodiment of the present application. Therefore, it should be emphasized and noted that "one embodiment" or "an embodiment" or "an alternative embodiment" mentioned twice or more in different positions in this specification does not necessarily refer to the same embodiment. In addition, some features, structures or characteristics in one or more embodiments of the present application can be appropriately combined.

[0061] In some embodiments, numbers describing the number of components and attributes are used. It should be understood that such numbers used in the description of the embodiments are modified by the modifiers "about", "approximately" or "substantially" in some examples. Unless otherwise specified, "about", "approximately" or "substantially" indicate that the numbers are allowed to vary by ±20%. Accordingly, in some embodiments, the numerical parameters used in the specification and claims are approximate values, which may change according to the required features of individual embodiments. In some embodiments, the numerical parameters should take into account the specified significant digits and adopt the general method of retaining digits. Although the numerical domains and parameters used to confirm the breadth of their range in some embodiments of the present application are approximate values, in specific embodiments, the setting of such numerical values ​​is as accurate as possible within the feasible range.

[0062] Although the present application has been described with reference to the current specific embodiments, ordinary technicians in this technical field should recognize that the above embodiments are only used to illustrate the present application, and various equivalent changes or substitutions may be made without departing from the spirit of the present application. Therefore, as long as the changes and modifications to the above embodiments are within the essential spirit of the present application, they will fall within the scope of the claims of the present application.

Claims

1. A method for preparing an electron transport layer, characterized in that: include: preparing a first mother solution, wherein the solute of the first mother solution is one or more stannous halide salts, and the solvent of the first mother solution is an acid containing a mercapto group; preparing a second mother liquor, wherein the solute of the second mother liquor is urea and the solvent of the second mother liquor is pure water; Mixing the first mother liquor and the second mother liquor, adding halogen acid, stirring and dissolving, to form a third mother liquor, wherein the halogen element in the halogen acid is the same as the halogen element in the stannous halide salt; A chelating agent is added to the third mother solution to dissolve and dilute it, and a substrate on which the electron transport layer is to be prepared is placed in the third mother solution containing the chelating agent to prepare the electron transport layer.

2. The method for preparing an electron transport layer according to claim 1, characterized in that: When preparing the first mother solution, the concentration of the first mother solution is between 3mmol / L and 5mmol / L.

3. The method for preparing an electron transport layer according to claim 2, characterized in that: When preparing the second mother solution, the concentration of the second mother solution is between 0.2 mmol / L and 0.3 mmol / L.

4. The method for preparing an electron transport layer according to claim 3, characterized in that: When preparing the third mother solution, the concentration of the hydrohalic acid is between 0.01 mmol / L and 1 mmol / L.

5. The method for preparing an electron transport layer according to claim 1, characterized in that: Placing the substrate on which the electron transport layer is to be prepared into the third mother solution containing the chelating agent, and preparing the electron transport layer comprises: The substrate on which the electron transport layer is to be prepared is placed in the third mother liquor containing the chelating agent. After the hydrolysis is completed, the substrate is rinsed with pure water, then subjected to ultrasonic treatment, dried, and then annealed to obtain a SnO2 electron transport layer.

6. The method for preparing an electron transport layer according to claim 5, characterized in that: The hydrolysis time after the substrate is placed in the third mother solution containing the chelating agent is between 1.5 hours and 2 hours, and / or the annealing temperature after drying is between 150° C. and 170° C.

7. The method for preparing an electron transport layer according to claim 5, characterized in that: In the step of adding a chelating agent to the third mother liquor to dissolve and dilute, the concentration of the chelating agent is between 0.3 mg / ml and 2 mg / ml.

8. The method for preparing an electron transport layer according to claim 1, characterized in that: The chelating agent is one or both of tetrasodium ethylenediaminetetraacetate and trisodium hydroxyethylethylenediaminetriacetate.

9. An electron transport layer, characterized in that The electron transport layer is prepared by the preparation method of the electron transport layer according to any one of claims 1 to 8.

10. A method for preparing a perovskite battery, characterized in that: include: Preparation of ITO conductive glass; The electron transport layer SnO2 is prepared by chemical bath deposition, wherein the electron transport layer SnO2 is prepared by the preparation method according to any one of claims 1 to 8; The FAPbI3 perovskite light-absorbing layer was prepared by spin coating; The hole transport layer Sprio-OMeTAD was prepared by spin coating; MoO3 was prepared by thermal evaporation method; The Ag electrode was prepared by thermal evaporation.

11. A perovskite battery, characterized in that: Prepared by the preparation method of claim 10, the perovskite battery structure comprises glass, a transparent conductive oxide layer, a SnO2 electron transport layer, a perovskite light absorption layer, a hole transport layer and an electrode in sequence.

12. The perovskite cell according to claim 11, characterized in that The transparent conductive oxide layer includes one of the following materials: ITO, IZO, IWO, FTO, ICO, AZO and BZO.

13. The perovskite cell according to claim 11, characterized in that: The perovskite light-absorbing layer has a thickness of 10 nm to 100 μm and a band gap of 0.9 eV to 3.0 eV.